CLASSROOM LANGUAGE FUNCTIONS USED BY EFL TEACHER DURING DISTANCE LEARNING IN JUNIOR HIGH SCHOOL - Cahyani, Ni Nyoman Bunga; Artini, Luh Putri; Wahyuni, Luh Gede Eka (E-Link Journal, 2023)
The purpose of this study is to describe the classroom language functions used by the EFL teacher in junior high school during distance learning. This study is classified as qualitative descriptive research. This research was conducted in SMP N 2 Sawan with only one subject, a grade 7 English teacher. The findings of this study showed that the EFL teacher preferred to implement ’seeking information’ as the highest classroom language function delivered during distance learning, followed by ’explaining’ by 21.88%, ’persuade’ came in third place with 20.31%. In fourth place is ’ordering’, with 17.19 percent. Next are ’evaluating’ (1.95%), ’comparing’ (1.56%), ’analyzing’ (1.17%), ’proving/debating’ (0.78%), justifying (0.78%), ’inferring’ (0.39%), and ’synthesizing’ (0.39%). Meanwhile, the teacher did not use two functions during teaching. They were ’classifying’ (0%) and ’solving problems’ (0%).